Generational Resonance in the Work Environment - Wątroba, Wiesław (Warsaw Forum of Economic Sociology, 2016)
The paper is an attempt to analyse the influence of generational differences on social relations and psycho-social atmosphere in the contemporary work environment. The starting point of this analysis is the category of Echo-Boomers, which is how the generation of Millennials (also named Generation Y) is called due to certain qualities that make them similar to Baby Boomers, who were born in the twenty years after World War II. The subject of this analysis are some overlapping areas of both generations regarding value systems, attitudes, as well as cultural practices related to professional activity and balance between work and the private sphere. The purpose of this analysis is to verify the hypothesis that there is a significant similarity between both generations, a generational resonance.